Study of the prevalence of metabolic syndrome among patients with polycystic ovary syndrome at Tishreen University Hospital - جديد يارا; أريج بوبو; ميسون ديوب (Latakia University Journal -Medical Sciences Series, 2024)
Background: Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders with 7-15% prevalence that affects women of reproductive age. Polycystic ovary syndrome (PCOS) and the metabolic syndrome have many features in common and may share the same pathogenesis. Recent studies have reported varied prevalence of metabolic syndrome (MetS) in women with PCOS. Objectives: The aim of the present study was to evaluate the prevalence of metabolic syndrome in women with polycystic ovary syndrome (PCOS). Methods and patients: All the women attending the endocrine clinic categorized as polycystic ovary syndrome according to Rotterdam criteria during the study period were included in the study. The women with PCOS underwent screening for metabolic syndrome as defined by the modified American Heart Association/ National Heart Lung Blood Institute (AHA/NHLBI) ATP 111 definition. A multivariate logistic regression analysis was applied and significant predictors identified for the prediction of metabolic syndrome. Results: The overall prevalence of metabolic syndrome according to the AHA/NHLBI ATP III criteria was 32.8%.The prevalence for individual components comprising the metabolic syndrome were :waist circumference greater than 88 cm in 56.6%, high-density lipoprotein cholesterol less than 50 mg/dl in 41.6%, triglycerides greater than or equal to 150 mg/dl in 33.8%, fasting glucose concentrations greater than or equal to 100 mg/dl in 13.8%,and blood pressure greater than or equal to 130/85 mm Hg in 12.8%. Conclusions: The metabolic syndrome and its individual components are common in PCOS, particularly among women with the central obesity.